Clinical follow-up of 2 families with glomerulopathy caused by COQ8B gene variants and literature review - Zhang, Lei; Hall, Gentzon; Han, Peitong; Li, Chunzhen; Cui, Jieyuan (Frontiers in Pediatrics, 2025)
BackgroundPrimary coenzyme Q10 (CoQ10) deficiency is an autosomal recessive genetic disease caused by mitochondrial dysfunction. Variants in Coenzyme Q8B (COQ8B) can cause primary CoQ10 deficiency. COQ8B-related glomerulopathy is a recently recognized glomerular disease that most often presents as steroid-resistant nephrotic syndrome (SRNS) in childhood. The disease often progresses to kidney failure and the renal histopathology is most commonly focal segmental glomerulosclerosis (FSGS).MethodsFour SRNS cases (2 females and 2 males) from 2 unrelated families who were followed clinically for nearly 3 years. Clinical exome testing and analyses were performed by MyGenostics Laboratory in China to evaluate unexplained proteinuria given the strong family history of glomerular disease and histologic evidence of SRNS. Pathogenic variants were identified in COQ8B in the exome studies and confirmed by direct sequencing.ResultsClinical exome sequencing revealed biallelic variants of the COQ8B gene in 2 families. In the Family 1, the oldest of three affected siblings died of renal failure at 11 years of age. Based on the results of genetic testing which identified a homozygous variant of COQ8B, the other two affected siblings with mild proteinuria and normal renal function were treated with CoQ10 oral supplementation at an early stage. Coenzyme Q10 treatment was effective in reducing proteinuria levels in both patients from Family 1 over the first 6 months and the two patients still have low-level proteinuria and normal renal function at nearly three years. In Family 2, clinical exome sequencing revealed a compoundheterozygous variants of COQ8B in a patient with biopsy- proven FSGS. His disease was unresponsive to prior treatment with glucocorticoids and cyclosporine. Oral CoQ10 was initiated based on his genetic diagnosis and was it was effective in reducing proteinuria over the first 5 months months of therapy. However after 1 year, his disease progressed tokidney failure. Kidney transplantation was performed at 5 years of age and his condition has been stable without rejection and no recurrence of disease.ConclusionsCOQ8B gene variant-related glomerulopathy often presents as SRNS without obvious extrarenal manifestations. The histopathology is mainly FSGS and follows an autosomal recessive mode of inheritance. Some patients may benefit from early coenzyme Q10 supplementation. For patients whose disease progresses to kidney failure, kidney transplantation can be an effective treatment. For children with unexplained proteinuria and abnormal renal function, genetic testing should be performed early in the course of disease to guide therapy where possible and improve prognosis.